Cultural and Social Dimensions Influencing Interaction through Social Media Networks in Saudi Society: A Field Study on a Sample of Social Media Users in Saudi Society - Alenizi, Saleh Zaid (Journal of Posthumanism, 2024)
This study aims to explore the cultural and social factors and dimensions identified by social identity theory, public sphere theory, and self-presentation theory that influence interaction through social media platforms in Saudi society. This study is based on several theoretical frameworks that address cultural and social dimensions, as well as audience interaction with media and communication content. Among these frameworks are identity theory and public sphere theory, which help understand the components of identity in the social environment. Public sphere theory, in particular, is based on the fundamental premise that "the public is active" in its ability to dialogue and debate issues of interest, which contributes to shaping public opinion that guides attitudes toward these issues. Despite the public’s ability to interact, its interaction is influenced by underlying social and cultural structures, as framed by identity and public sphere theories. These frameworks shape the criteria for audience engagement and interaction with media and communication messages across social media platforms. It also discusses self-presentation theory, whereby individuals seek to manage how they present themselves on social media platforms by engaging with various societal issues. Accordingly, the research examines the impact of these factors on the nature and extent of engagement across different forms of social media engagement, and assesses the degree to which these factors shape the level and nature of user engagement with content posted on social media platforms.